Pengembangan Permen Jelly Berbahan Dasar Minuman Tradisional Loloh Cemcem (Spondias pinnata (L.f) Kurz) Dengan Penambahan Sari Kunyit (Curcuma domestica Val.) yang Berpotensi sebagai Pangan Fungsional - Dewi, Ni Luh Ayu Arta Suari; Puspawati, Gusti Ayu Kadek Diah; Pratiwi, I Desak Putu Kartika (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 4 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i04.p08, 2024)
Loloh cemcem is a traditional Balinese drink, that contains bioactive compounds which potentially give functional effect. Loloh cemcem can be processed into jelly candy, but the process causes a decrease in antioxidant so it is required to add ingredient that can support the antioxidant activity, which is turmeric juice. This research aims to determine the effect of turmeric juice adding on the characteristics of loloh cemcem jelly candy and obtaining turmeric juice adding concentration that produce a loloh cemcem jelly candy with the best characteristic that potential as a functional food source of antioxidant. This research used a Complete Random Design (CDR) with the addition of turmeric juice which consists of 5 concentrations: 0%, 10% ,20%, 30% and 40% with 3 repetition in each treatment. The data obtained were analyzed with analysis of variance, treatments that had a significant effect were continued using Duncan Multiple Range Test (DMRT). As shown by the result, the addition of turmeric juice had a significant effect on color, water content, antioxidant activity, total flavonoid, curcumin content, hedonic test of color, taste, odor, and overall acceptance also scoring test of color and taste. Addition turmeric juice with concentration 30% produce the best characteristic with color intensity L 25,67, a* 14 and b*35,33 as an eyelash camel color, water content 22,45%, ash content 0,46%, antioxidant activity 49,56%, total flavonoids 1,47 mg QE/g, curcumin content 0,16%, reducing of sugar 23,47%, sensory properties color is slightly yellow and liked, the odor is liked, the taste is a bit typical of turmeric and liked, the texture slightly liked, and overall acceptance is liked. The presence of antioxidant activity of 49,56% makes jelly candy with the addition of 30% turmeric juice have the potential as a functional food source of antioxidant. Keywords : loloh cemcem, antioxidant, jelly candy, turmeric juice, functional food